The impacts of anomalies in atmospheric circulations on Arctic sea ice outflow and sea ice conditions in the Barents and Greenland seas: case study in 2020 - Zhang, Fanyi; Lei, Ruibo; Zhai, Mengxi; Pang, Xiaoping; Li, Na (The Cryosphere, 2023)
Arctic sea ice outflow to the Atlantic Ocean is essential to the Arctic sea ice mass budget and the marine environments in the Barents and Greenland seas (BGS). With the extremely positive Arctic Oscillation (AO) in winter (JFM) 2020, the feedback mechanisms of anomalies in Arctic sea ice outflow and their impacts on winter–spring sea ice and other marine environmental conditions in the subsequent months until early summer in the BGS were investigated. The results reveal that the total sea ice area flux (SIAF) through the Fram Strait, the Svalbard–Franz Josef Land passageway, and the Franz Josef Land–Novaya Zemlya passageway in winter and June 2020 was higher than the 1988–2020 climatology. The relatively large total SIAF, which was dominated by that through the Fram Strait (77.6 %), can be significantly related to atmospheric circulation anomalies, especially with the positive phases of the winter AO and the winter–spring relatively high air pressure gradient across the western and eastern Arctic Ocean. Such abnormal winter atmospheric circulation patterns have induced wind speeds anomalies that accelerate sea ice motion (SIM) in the Atlantic sector of Transpolar Drift, subsequently contributing to the variability in the SIAF ( R=+0.86, P<0.001). The abnormally large Arctic sea ice outflow led to increased sea ice area (SIA) and thickness in the BGS, which has been observed since March 2020, especially in May–June. The increased SIA impeded the warming of the sea surface temperature (SST), with a significant negative correlation between April SIA and synchronous SST as well as the lagging SST of 1–3 months based on the historic data from 1982–2020. Therefore, this study suggests that winter–spring Arctic sea ice outflow can be considered a predictor of changes in sea ice and other marine environmental conditions in the BGS in the subsequent months, at least until early summer. The results promote our understanding of the physical connection between the central Arctic Ocean and the BGS.